2010
DOI: 10.1007/s00497-010-0138-8
|View full text |Cite
|
Sign up to set email alerts
|

Strong post-pollination pre-zygotic isolation between sympatric, food-deceptive Mediterranean orchids

Abstract: Mediterranean orchids that grow in admixed, co-flowering populations, and frequently show hybrid progenies are interesting to use to study the nature and the strength of post-zygotic barriers. However, examination of pre- and post-pollination pre-zygotic isolating mechanisms requires sympatric, co-flowering species pairs that do not produce hybrid swarms. In this study, we analyzed a contact zone between Orchis italica and O. papilionacea, in which hybrid forms have never been reported, although hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…() suggested that prezygotic barriers contributed more to reproductive isolation than postzygotic barriers. This hypothesis was supported in other studies (Lowry, Rockwood et al., ; Pellegrino, Bellusci, & Musacchio, ; Sobel & Streisfeld, ; Xu et al., ), but there are important exceptions in some lineages (Borba, Shepherd, & Semir, ; Chen, Luo, & Zhang, ; Costa, Lambert, Borba, & de Queiroz, ; Silva‐Pereira, de Camargo Smidt, & Borba, ). For example, low F 1 germination rates and F 1 pollen sterility, as components of postzygotic isolation, were crucial for reproductive isolation between Mussaenda pubescens var.…”
Section: Introductionsupporting
confidence: 63%
“…() suggested that prezygotic barriers contributed more to reproductive isolation than postzygotic barriers. This hypothesis was supported in other studies (Lowry, Rockwood et al., ; Pellegrino, Bellusci, & Musacchio, ; Sobel & Streisfeld, ; Xu et al., ), but there are important exceptions in some lineages (Borba, Shepherd, & Semir, ; Chen, Luo, & Zhang, ; Costa, Lambert, Borba, & de Queiroz, ; Silva‐Pereira, de Camargo Smidt, & Borba, ). For example, low F 1 germination rates and F 1 pollen sterility, as components of postzygotic isolation, were crucial for reproductive isolation between Mussaenda pubescens var.…”
Section: Introductionsupporting
confidence: 63%
“…and Dactylorhiza spp., pollen tubes grow through the stigma surface and into the top of the ovary within 2 or 3 days (Neiland & Wilcock ; Pellegrino et al . ). In our case, heterospecific pollen remains for at least 36–48 h before moving into the ovary and if, in the meantime, conspecific pollen arrives on the stigma, this stops heterospecific pollen tube development; thus, there is an advantage of conspecific pollen fertilising ovules as pollen tubes grow faster than those of heterospecific pollen.…”
Section: Discussionmentioning
confidence: 97%
“…The diploid cytotype is genetically more distant from the polyploids than tetraploids and hexaploids are from each other (M. Winkler et al, unpublished data). Therefore, Bateson-Dobzhansky-Muller incompatibilities [75] , pollen-pistil incompatibilities and/or impaired pollen tube growth [76] , or nuclear-cytoplasmic interactions [77] may play a role as well.…”
Section: Discussionmentioning
confidence: 99%